Investigation of different MCS selection algorithm to reduce the impact of CSI-RS on LTE legacy UEs - Zhao, Xiaofei; Gu, Xinyu; Zhang, Xiang; Gong, Yi; Zhang, Lin; Li, Wenyu (TENCON ... IEEE Region Ten Conference, 2015)
In LTE-A (Long Term Evolution-Advanced) network deployed with higher order MIMO (Multiple Input Multiple Output), CRS (Common Reference Signal) is substituted by CSI-RS (Channel State Information Reference Signal) aiming for detecting channel more efficiently. But LTE (Long Term Evolution) legacy UEs (User Equipment) cannot distinguish CSI-RS from data which may deteriorate the LTE UEs' demodulation performance. And in CoMP (Coordinated Multiple Point Transmission) scenario the number of REs (Resource Element) occupied by CSI-RS will be multiplied, in which case the demodulation performance would be even worse. So the introduction of CSI-RS makes it troublesome for LTE legacy UEs scheduled in the LTE-A network. Simulation results by both link-level and system-level reveal that LTE legacy UEs' performance is more seriously degraded due to the impact of CSI-RS when the coding rate and modulation order go higher. In this paper we propose and compare different MCS (Modulation Coding Scheme) selection algorithms about reducing the impact of CSI-RS on LTE legacy UEs scheduled in LTE-A network. SLA (Smart Link Adaptation) algorithm relys on manned control too much for different scenarios. IE-SINR (Interpolation Empirical SINR) algorithm is applicable to different scenarios while it cannot improve system performance as much as SLA algorithm. VSE (Valid Spectrum Efficiency) algorithm is a more general method and can adapt to different scenarios and simulation results show that VSE algorithm can improve system throughput not lower than SLA algorithm.